Preparation and evaluation of an injectable curcumin loaded chitosan/hydroxyapatite cement. (May 2021) - Wu, Feipeng; Zhao, Hongxia; Shi, Jiahui; Long, Lang; Yang, Zhiqiang; Jin, Hua; Hou, Xuedan
Curcumin (Cur) is an active ingredient of Curcuma longa. Cur has many pharmacological effects, such as anti-inflammation, anti-oxidation, anticoagulation, hypolipidemic, anti-angiogenesis and anti-cancer. An injectable curcumin loaded chitosan/hydroxyapatite bone cement (Cur-CS/HA) was prepared as a bone scaffold and drug delivery. Tween 20, a nonionic surfactant, was incorporated into the cement to improve the solubility of curcumin. Four types of Cur-CS/HA (Group0, Group1, Group5 and Group10) were prepared with different Tween 20 ratios (0, 1, 5 and 10%, respectively). The samples were characterized by infrared spectroscopy (IR), X-ray diffraction (XRD) and scanning electron microscope (SEM). Compression tests were carried out to evaluate the strength of the scaffolds. In addition, the inhibition assay was carried out on MG63 cells with the extracts of drug loaded materials. The results showed that Cur had an effect on the setting time (p < 0.05). Cur reduced the compressive strength of the CS/HA cement (p < 0.05). The release studies showed that Tween 20 could effectively improve the solubility of curcumin. When the Tween 20 content in cement increased from 0 to 10%, the cumulative release (30 d) of Cur increased from 5.5 to 10.6%. Moreover, the cement had good injectability, good anti-collapsibility and good biocompatibility to meet the clinical requirements. The result of inhibition assay showed that Cur-CS/HA could inhibit the proliferation of MG63 cells. Tween 20 incorporated Cur-CS/HA had great potential to use as a drug-loaded artificial bone material.